Metabolic dysfunction impairs Mycobacterium tuberculosis-specific cytokine and chemokine responses in latent tuberculosis and type 2 diabetes mellitus - Phillip Ssekamatte; Diana Sitenda; Rose Nabatanzi; Gyaviira Nkurunungi; Marjorie Nakibuule; Davis Kibirige; Andrew Peter Kyazze; David Patrick Kateete; Bernard Ssentalo Bagaya; Obondo James Sande; Reinout van Crevel; Stephen Cose; et al. (Scientific Reports)
Abstract Type 2 diabetes mellitus (DM) is associated with impaired host immune responses, increasing the risk for latent tuberculosis (TB) infection (LTBI). This study investigated how DM and associated metabolic dysfunction alter Mycobacterium tuberculosis (Mtb)-specific cytokine and chemokine responses. We analysed a cohort of 164 participants with and without DM and/or LTBI. Mtb-specific cytokine/chemokine responses were measured in QuantiFERON-TB Gold-Plus supernatants using a 17-plex Luminex assay to quantify Th1, Th2, Th17, inflammatory and regulatory responses. DM was associated with decreased Mtb-specific IFN-γ, TNF, IL-12, IP-10 and MIP-1α, with increased IFN-α compared to non-DM, suggesting impairment of Th1 and inflammatory pathways. Additionally, pre-DM was not associated with altered cytokine/chemokine responses, but subtle changes in IL-10, GM-CSF, MIP-1β, and IL-1β may suggest early indicators of immune dysregulation. Poorly controlled DM was associated with increased IL-4 and IFN-α, indicating a shift toward Th2 and inflammatory responses. Compared to borderline high, high total cholesterol levels, indicating dyslipidaemia, were associated with decreased IFN-γ, TNF and IL-2, suggesting impaired Th1 immunity. These findings imply that metabolic disturbances may compromise Mtb-specific immune responses, potentially increasing TB infection susceptibility. Optimising glycaemic and lipid control may be crucial for restoring immune balance and improving TB outcomes in patients with DM-associated metabolic dysfunction.